Pengaruh Upah Minimum Terhadap Penyerapan Tenaga Kerja di Indonesia Tahun 2015-2020 - Asmara, Gea Dwi; Saleh, Rahmat; Asmara, Galuh Jati (Journal of Advances in Accounting, Economics, and Management, 2024)
The rapid increase in the number of the workforce in Indonesia which is not matched by the number of available jobs will cause unemployment, therefore policies are needed that are able to increase labor absorption and also reduce unemployment. This study aims to analyze the effect of the minimum wage on labor absorption in Indonesia. The data used in the form of secondary data obtained from the Central Statistics Agency. This study uses the independent variable of the provincial minimum wage with the control variables namely education and GRDP of each province. The dependent variable used is labor absorption. This study uses panel data using the fixed effect model for the 2015-2020 period in 34 provinces in Indonesia. In this study, it was found that the provincial minimum wage had a positive effect on employment in Indonesia in 2015-2020. In addition, the control variables of education and GRDP also have a positive influence on employment.